Toxoplasma gondii: Evaluation of an intranasal vaccine using recombinant proteins against brain cyst formation in BALB/c mice - Igarashi, M.; Kano, F.; Tamekuni, K.; Machado, R. Z. [UNESP]; Navarro, I. T.; Vidotto, O.; Vidotto, M. C.; Garcia, J. L. (Academic Press Inc. Elsevier B.V., 2008)
The purpose of this work was to evaluate protective activity against brain cyst formation in BALB/c mice intranasally vaccinated with recombinant proteins from Toxoplasma gondii. The recombinant proteins rROP2, rGRA5 and rGRA7 were used in vaccine preparation. Thirty-three female mice were divided into three groups, these animals received two doses by intranasal route at days 0 and 21 as follows; group 1 (G1, n = 11) received 12.5 mu g of each recombinant protein plus 0.5 mu g of cholera toxin, group 2 (G2, n = 11) received phosphate buffer saline (PBS) plus 0.5 mu g of cholera toxin, and group 3 (G3, n = 11) received PBS only. At challenge day (day 33) three animals from each group were euthanatized for IgA measure from intestine. Mice were infected orally with 50 cysts from the VEG strain at day 33. At challenge day the G1 animals had high immunoglobulin A levels, however, they only showed IgG antibody titers against rROP2 and rGRAT Animals from G1 also exhibited strong resistance to cyst formation compared with the control group (G3, P < 0.05). However, we did not observe differences in protection against brain cyst formation between G1 and G2 (P > 0.1). These results indicate that intranasal immunization in BALB/c mice with recombinant proteins rROP2, rGRA5 and rGRA7 associated with cholera toxin induced partial protection, when compared with G3, against tissue cyst formation after oral infection with tissue cysts from T gondii. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Toxoplasma gondii; mouse; recombinant proteins; rhoptry; dense granule; Vaccine